P742 Iranian Registry of Crohn's and Colitis (IRCC): first nation-wide IBD registry in Middle East, a study protocol. (25th January 2019) - Malekzadeh, M; Sima, A; Alatab, S; Sadeghi, A; Ebrahimi Daryani, N; Adibi, P; Maleki, I; Vossoughinia, H; Fakheri, H; Yazdanbod, A; Taghavi, S A; Aghazadeh, R; et al.
Abstract: Background: A recent nation-wide study of inflammatory bowel disease (IBD) from Iran revealed a rapidly increasing incidence and prevalence. The best epidemiologic study to assess the burden and improve the care of IBD is a Population-based registry. The Iranian Registry of Crohn's and Colitis (IRCC) was established recently to answer the needs. We aimed to report the design, methods of data collection, and aims of IRCC to enlighten the strengths and limitations of this project. Methods: IRCC is multi-centre prospective registry, which is established with collaboration of about 100 gastroenterologists who are providing care for IBD patients in different provinces of Iran. Minimum data set for IRCC was defined according to an international consensus on standard set of outcomes for IBD. The questionnaire was designed accordingly in order to make the data collection feasible in clinical setting. Feasibility of study was tested using a pilot study on 553 IBD patients with a web-based questioner. During and after the pilot study many revisions was made on questionnaire and software according to feedback of registrars and members of IRCC. The reliability of each section of questionnaire evaluated by Cronbach's α. For testing effect of any risk factor or specific condition or treatment on subtypes of IBD or disease activity we used chi square test and ANOVA. P-value less than 0.05 considered significant. Results: In pilot study, 312 (56.4%) of participants were male and mean age was 38 years (Standard deviatio n = 12.8) and 378 (68.35%) patients had ulcerative colitis, 303 (54.7%) had college education and 358 (64.74%) were of Fars ethnicity. Among this sample, 68 (12.3%), 44 (7.9%), 13 (2.3%) of participants were smokers, hookah and opium users, respectively. History of appendectomy was reported in 58 (10.48%) of patients. The most consumed drug was 5-ASA (94.39%). The reliability of each section of questionnaire were checked and most sections had α>0.6. We established a well-designed registry with standard data set in order to better study IBD in Iran. Conclusions: To best of our knowledge, IRCC is the first national level IBD registry running in Middle East and could become a reliable infrastructure for national and international research on IBD and at the same time improve the care of IBD patients and provide national information for policy makers to better plan for controlling IBD in Iran.